Evaluación del desempeño de los modelos de tráfico autosimilares en redes IEEE 802.11 - caso de estudio red QRD (2012)
This paper evaluates the performance of fractal or self-similar traffic models in IEEE 802.11 networks. This study is focused on the “Quindio Región Digital” (QRD) network. Performance evaluation of the traffic models is performed in three stages. In the first stage, we obtain the statistical characteristics of the current traffic on the QRD network. In the second stage, the most suitable traffic models are selected for the current characteristics of the QRD network such as out- of-saturation operation and management of heterogeneous traffic. In the third stage, we define a performance metric that is used to evaluate the traffic patterns through simulation..